2013
DOI: 10.1186/1471-2458-13-1230
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a cardiovascular health awareness program (CHAP) on reducing blood pressure: a prospective cohort study

Abstract: BackgroundHypertension is an important and modifiable cardiovascular risk factor that remains under-detected and under-treated, especially in the older individuals. Community-led interventions that integrate primary health care and local resources are promising approaches to improve awareness and management of hypertension and other cardiovascular risk factors. We aimed to evaluate the effect of a community-based Cardiovascular Health Awareness Program (CHAP) on participants’ blood pressure.MethodsThis study f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Community resources such as volunteers, health nurses, and local organizations are underutilized to support disease prevention and primary health care. Synergy created by connecting family physicians, patients, peer volunteers and local resources can lead to better health outcomes for community residents [33] .…”
Section: Discussionmentioning
confidence: 99%
“…Community resources such as volunteers, health nurses, and local organizations are underutilized to support disease prevention and primary health care. Synergy created by connecting family physicians, patients, peer volunteers and local resources can lead to better health outcomes for community residents [33] .…”
Section: Discussionmentioning
confidence: 99%
“…33,34 All of these individual changes may have led to the significant difference in ambulance calls between intervention and control groups. Extrapolation suggests that an average of 10 to 11 calls per 100 apartment units would be avoided each year.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study performed by Dolovich et al . has demonstrated that the cardiovascular health awareness program (CHAP) is associated with a reduction in systolic and diastolic blood pressure [ 19 ]. Our recent study also proves that ideal cardiovascular health behaviors and factors play a prevent role on the development of hypertension [ 20 ].…”
Section: Introductionmentioning
confidence: 99%